“Decipher its noises for us”: Understanding Sycorax’s Island in Marina Warner’s Indigo - Presley, Erin M. (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2012)
The Marina Warner’s novel Indigo, or Mapping the Waters (1992) explores the effects of colonialism on the islanders of Liamuiga and the Everard family through a complex retelling of Shakespeare’s The Tempest that spans over three hundred years. Much like the appropriative novels of Gloria Naylor, in which past and present blend and meld, Indigo also suggests that time is not linear in its development. The subtitle, or Mapping the Waters, positions a sense of place at the crux of Warner’s novel. Moving back and forth between the twentieth century and the dawn of the seventeenth century, the novel also shifts between London and the Caribbean, suggesting the global import of Shakespeare’s late romance. The scene, in the Burkean sense, influences the actions of the characters as they struggle to be heard in their respective settings. Language also affects the ways in which these characters come to terms with their personal histories. Ultimately, the novel seeks to displace the hopelessness of Caliban’s decree in The Tempest —“You taught me language, and my profit on’t / Is I know how to curse” (1.2.364-65)— by giving a voice to the people silenced by colonialism.